Analisis Fundamental Terhadap Harga Saham Pada Saat Pandemi: (Studi Kasus Pada Perusahaan LQ45 Tahun 2020- 2021 Yang Terdaftar Di Bursa Efek Indonesia) - Ronald N Girsang (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The COVID-19 pandemic caused the BEI sectoral index to experience declines and increases in share prices during the 2020 period. This research aims to provide fundamental analysis of share prices. Case Study of the 2020-2021 LQ45 Company Listed on the Indonesian Stock Exchange. The population in this research was 45 companies, and based on the sample selection criteria above, the research sample was 19 companies and the total amount of data examined was 38 data. The results of this research are to partially explain the variables Debt To Equity Ratio, Price To Book Value, Return On Equity, Price Earning Ratio, And Earnings per share which simultaneously influence Stock Prices. Meanwhile, partially the Debt To Equity Ratio and Price Earning Ratio have no effect on Stock Prices, while price to book value, return on equity, and Earnings Per Share partially have an effect on stock prices.